Dano à ordem urbanística em Salvador - Ba - Brasileiro, Gabriel Galvão (2016)
Cities, living spaces and inhabited by individuals, are constituted as the materialization of the processes and social and spatial relationships, and so permanently is changing. The urban order arises from the relationship between the right and the cities, aiming to make them better, fairer and more democratic for the entire community. Damage to urban order reach diffuse and collective interests, so should be avoided and combated. This study aims to understand the damage from the analysis how and under what conditions the damage occurs urban order in the city of Salvador. The data used were the civil investigations, that calculate the offense or violation of urban order in the city of Salvador, and the Public Civil Actions that aim to blame, repair and contain or reverse the damage caused to this order, both initiated by the Prosecutor's Office of housing and Bahia prosecutors Urbanism, from 2008 to 2014. the results show that the protection of urban order has not been effective, given the large amount and complexity of the damage to the urban order. Such damage has been generated by actions motivated by private interests or by omission and failures of public administration, and materialize, spatially in different ways.